2015
DOI: 10.1002/2015gl063303
|View full text |Cite
|
Sign up to set email alerts
|

Multiannual forecasts of Atlantic U.S. tropical cyclone wind damage potential

Abstract: There are strong decadal variations in Atlantic hurricane activity, with an active period in the 1950s and 1960s, a quiescent period from the 1970s through the early 1990s and a resurgence in activity since the mid‐1990s. Using an index that relies on subpolar gyre temperature and subtropical sea level pressure, two quantities with links to hurricane activity, we show that it is possible to construct reliable 5 year mean forecasts of both basin‐wide tropical cyclone activity as well as wind energy associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In the Atlantic Ocean, the AMV is the dominant mode of decadal climate variability and has been linked to several climate impacts over Europe, North America and the Sahel (Zhang and Delwoth, 2006;Sutton and Dong, 2012;Ruprich-Robert et al, 2017 as well as to Atlantic tropical cyclones (e.g. Caron et al, 2015Caron et al, , 2018. Both PRED and HIST are capable of skilfully predicting the AMV, and they show better performance than a persistence forecast (except for the forecast range from 1 to 4 years in HIST), as shown by the ACC (Fig.…”
Section: Skill For the Main Ocean Modes Of Variabilitymentioning
confidence: 97%
“…In the Atlantic Ocean, the AMV is the dominant mode of decadal climate variability and has been linked to several climate impacts over Europe, North America and the Sahel (Zhang and Delwoth, 2006;Sutton and Dong, 2012;Ruprich-Robert et al, 2017 as well as to Atlantic tropical cyclones (e.g. Caron et al, 2015Caron et al, , 2018. Both PRED and HIST are capable of skilfully predicting the AMV, and they show better performance than a persistence forecast (except for the forecast range from 1 to 4 years in HIST), as shown by the ACC (Fig.…”
Section: Skill For the Main Ocean Modes Of Variabilitymentioning
confidence: 97%
“…More recently, Caron et al showed that multi‐year prediction of Atlantic hurricane activity by CMIP5 models in hindcast mode had modest positive skill, even after accounting for persistence in the climate shift that occurred in 1994–1995. The potential for predicting possible wind damage related to hurricanes along the U.S. coast using a multi‐model ensemble of initialized global climate models has also been recently demonstrated . Decadal predictability of TC activity is a new field and it is expected that more modeling groups will explore this topic in the next few years.…”
Section: Current State‐of‐the‐art Global Climate Models: From Intrasementioning
confidence: 99%
“…Although the aforementioned climate variables are arguably the most well‐known modulators of Atlantic tropical cyclone activity, hurricane activity has also been linked to the North Atlantic Oscillation (NAO) [ Elsner and Kocher , ; Elsner et al , ; Villarini et al , ], the 11 year solar cycle [ Hodges and Elsner , ; Elsner and Jagger , ], natural and anthropogenic tropospheric aerosols [ Dunstone et al , ; Evan et al , , ], and the North Atlantic subpolar gyre temperature [ Smith et al , ; Dunstone et al , ; Caron et al , ].…”
Section: Introductionmentioning
confidence: 99%